Evaluation of Impulse Oscillometry in Respiratory Airway Casts with Varying Obstruction Phenotypes, Locations, and Complexities - Xiuhua Si; Jensen S. Xi; Mohamed Talaat; Ramesh Donepudi; Wei-Chung Su; Jinxiang Xi (MDPI AG, 2022)
The use of impulse oscillometry (IOS) for lung function testing does not need patient cooperation and has gained increasing popularity among both young and senior populations, as well as in patients with breathing difficulties. However, studies of the IOS sensitivity to regional lung obstructions are limited and have shown mixed results. The objective of this study was to evaluate the performance of an IOS system in 3D-printed lung models with structural abnormalities at different locations and with different severities. Lung trees of two complexity levels were tested, with one extending to the sixth generation (G6) and the other to G12. The IOS responses to varying glottal apertures, carina ridge tumors, and segmental bronchial constrictions were quantified in the G6 lung geometry. Both the G6 and G12 lung casts were prepared using high-resolution 3D printers. Overall, IOS detected the progressive airway obstructions considered in this study. The resonant frequency dropped with increasing obstructions for all three disease phenotypes in the G6 lung models. R20Hz increased with the increase in airway obstructions. Specifically, R20Hz in the airway model with varying glottal apertures agreed reasonably well with complementary measurements using TSI VelociCalc. In contrast to the high-resistance (R) sensitivity to the frequency in G6 lung models, R was nearly independent of frequency in G12 lung models. IOS R20Hz demonstrated adequate sensitivity to the structural remodeling in the central airways. However, the changes of R5Hz and X5Hz vs. airway obstructions were inconclusive in this study, possibly due to the rigid lung casts and the difference of a container-syringe system from human lungs.